Perception of support provided for people with traumatic brain injury in relation to caregiver burden : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Fraser, Julie Rebecca (Massey University, 2003)
This study explores caregiver perceptions of social supports provided for people with Traumatic Brain Injury (TBI) in relation to caregiver burden. Twenty-four people acting as primary caregivers of a person with TBI completed measures of social support and caregiver distress (Head Injury Behaviour Scale and a social support questionnaire developed specifically for this study). The domains assessed included the nature and number of treatment services utilized by the TBI person and caregivers' perceptions of these, the problems exhibited by the TBI person, and the distress experienced by the caregiver. Significant correlations were found between caregiver distress and the following variables: number of problems exhibited by the TBI person, change in caregiver employment status, helpfulness of treatment services for TBI person, and overall caregiver satisfaction. Regression analyses revealed that the number of problems exhibited by the TBI person and lack of helpfulness of treatment services were significant predictors of caregiver distress. These correlations and regressions were interpreted with respect to the buffering hypothesis and the Stress Appraisal Coping model (SAC). It was concluded that caregiver perception of social support rather than social support per se, is associated with caregiver distress, and that caregiver perception can buffer or attenuate caregiver distress. Methodological considerations and directions for future research are discussed.
Keywords: New Zealand; Brain -- Wounds and injuries; Patients -- Services for